2012
DOI: 10.1258/shorts.2011.011130
|View full text |Cite
|
Sign up to set email alerts
|

Patients undergoing blood tests before minor/moderate trauma surgery: a retrospective review

Abstract: ObjectiveThe aim of this study was to establish the number of unnecessary preoperative blood tests undertaken on ASA Grade 1 patients undergoing minor/moderate orthopaedic trauma surgery.DesignReview of all ASA1 patients who had been operated on the trauma lists for three consecutive months.SettingUK Teaching Hospital.ParticipantsPatients with ages ranging between 16 and 60 years, and undergoing a minor or moderate trauma operation.Main outcome measuresThe type and number of blood tests were established and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…This study is limited by the fact the relationship between blood requesting and overall mortality and morbidity was not investigated The literature however demonstrates that, in scheduled patients, management is unlikely to be influenced by blood tests particularly in healthy patients [3]. In a systematic review of preoperative testing by Munro et al, aberrations in haematology, haemaostasis tests and biochemistry changed the management of fewer than 1% of patients [15].…”
Section: Discussionmentioning
confidence: 95%
“…This study is limited by the fact the relationship between blood requesting and overall mortality and morbidity was not investigated The literature however demonstrates that, in scheduled patients, management is unlikely to be influenced by blood tests particularly in healthy patients [3]. In a systematic review of preoperative testing by Munro et al, aberrations in haematology, haemaostasis tests and biochemistry changed the management of fewer than 1% of patients [15].…”
Section: Discussionmentioning
confidence: 95%
“…Trials in children and many studies in adults support the need for selectivity for the tests to be performed in elective and non-cardiac surgery. 3,4 Those studies concluded that many and unnecessary preoperative tests have been used that increased the costs of the procedures. 3,4 Performing whole blood count preoperatively is a widely accepted opinion.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were based on case series (n=33) 22,31,33,34,36,38,41,[43][44][45][46][47][48][49][50]56,57,[60][61][62][63][64]66,[68][69][70][71][72]74,75,7785,89,90 followed by systematic reviews with or without meta-analysis (n=12) [23][24][25]28,29,39,53,59,67,78,83,86,88,91 , prospective cohorts (n=9) 30,32,35,37,42,…”
Section: Study Characteristics According To Categories Of Low Value Practicesmentioning
confidence: 99%
“…52,58 Methodological Quality of the Studies Studies focusing on initial diagnostic imaging were mostly of low to moderate quality or had serious to critical risk of bias (Table 2). One study on preoperative blood tests in ASA grade I patients respected 9/10 cases series quality criteria 22 , while another met half of these criteria. 38 Among studies on initial consultation and therapeutic interventions (Table 3), those on spine consultation after a thoracolumbar transverse process fracture had serious risk of bias.…”
Section: Study Characteristics According To Categories Of Low Value Practicesmentioning
confidence: 99%
See 1 more Smart Citation